2022
DOI: 10.3389/fbioe.2022.1082794
|View full text |Cite
|
Sign up to set email alerts
|

MRI-based machine learning model: A potential modality for predicting cognitive dysfunction in patients with type 2 diabetes mellitus

Abstract: Background: Type 2 diabetes mellitus (T2DM) is a crucial risk factor for cognitive impairment. Accurate assessment of patients’ cognitive function and early intervention is helpful to improve patient’s quality of life. At present, neuropsychiatric screening tests is often used to perform this task in clinical practice. However, it may have poor repeatability. Moreover, several studies revealed that machine learning (ML) models can effectively assess cognitive impairment in Alzheimer’s disease (AD) patients. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Low‐variance characteristics are identified by setting a threshold. Features with a variance below the threshold are deleted (Muhammad et al., 2021; Zhigao et al., 2022). A threshold variance of 0.8 was chosen based on the threshold variance method to retain features more likely to be relevant and contribute significantly to the model's performance.…”
Section: Methodsmentioning
confidence: 99%
“…Low‐variance characteristics are identified by setting a threshold. Features with a variance below the threshold are deleted (Muhammad et al., 2021; Zhigao et al., 2022). A threshold variance of 0.8 was chosen based on the threshold variance method to retain features more likely to be relevant and contribute significantly to the model's performance.…”
Section: Methodsmentioning
confidence: 99%
“…Metabolic syndromes, such as obesity and diabetes, have been associated with an increased risk of neuropsychiatric disorders, such as AD, PD, and Huntington's disease. Both human and animal studies have been utilized to explore the concurrence of neuropsychiatric disorders and metabolic diseases, revealing shared pathophysiological mechanisms, such as dyslipidemia (Yu et al, 2020), insulin resistance (Ma et al, 2022), neurovascular dysfunction (Xu et al, 2022), neuronal cell loss (Bharadwaj et al, 2017), and tubulin-associated unit (tau) phosphorylation (Freude et al, 2005). Song et al found that the number of patients with cognitive decline due to metabolic imbalances has increased considerably (Song, 2023).…”
Section: Metabolic Regulationmentioning
confidence: 99%
“…In recent studies, radiomics approaches have shown promising performance in the directions of type 2 diabetes mellitus (Xu et al, 2022 ) and breast cancer (Huang et al, 2021 ), while also demonstrating excellent performance in the diagnosis of temporal lobe epilepsy (TLE) using MRI (Mo J. et al, 2019 ; Park et al, 2020 ; Cheong et al, 2021 ) and PET (Zhang et al, 2021 ) images. In radiomics method that focus on pediatric FCD research, a particularly relevant study employed a two-stage Bayes classifier (Kulaseharan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%